Anterior cruciate ligament injury, prophylaxis and surgical reconstruction: A literature review (Research, Society and Development, 2024)
Introduction: Anterior cruciate ligament (ACL) injury is one of the most common and debilitating sports injuries, significantly affecting knee function and patient quality of life. Prophylaxis and surgical reconstruction are essential for effective prevention and treatment of this condition. This article reviews the literature on ACL injury prophylaxis and current surgical reconstruction approaches. Objectives: The objective of this article is to review prophylactic strategies for the prevention of ACL injuries and available surgical reconstruction techniques. The review aims to identify the most effective methods for reducing injury incidence and evaluate best practices for ACL reconstruction, considering factors such as graft choice, rehabilitation protocols, and postoperative outcomes. Results: The analysis revealed that prophylactic programs, including neuromuscular and proprioceptive training, are effective in reducing ACL injury incidence, with recommendations for their implementation in athletes. Regarding surgical reconstruction, comparisons between graft methods, such as patellar tendon and hamstring tendons, showed that using four-strand hamstring tendons provides similar or superior results to patellar tendon, with less morbidity. Intensive rehabilitation protocols, started early, were associated with better functional outcomes and fewer complications. Conclusion: Effective prophylaxis and careful selection of surgical technique are crucial for managing ACL injuries. The combination of well-structured prevention programs and careful choice of reconstruction method, along with an appropriate rehabilitation protocol, can significantly improve clinical outcomes and patient quality of life. Continued research and adoption of evidence-based practices are essential to optimize the treatment and prevention of these injuries.